Compact Embeddings for Spaces of Forward Rate Curves. (3rd October 2013) - Tappe, Stefan
Abstract : The goal of this paper is to prove a compact embedding result for spaces of forward rate curves. As a consequence of this result, we show that any forward rate evolution can be approximated by a sequence of finite dimensional processes in the larger state space.